Analisis Strategi Pemasaran dalam Meningkatkan Omzet Penjualan pada Usaha Apotek Aditara 2 Surabaya - Taradiva Adisty; Budi Prabowo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this research is to analyze and understand the implementation of the best marketing strategies at Apotek Aditara 2 in Surabaya. This research employs a descriptive method with a qualitative approach implemented through SWOT analysis and data collection techniques involving in-depth interviews, observations, and documentation related to the 7P marketing strategy, namely product, place, price, promotion, people, process, and physical evidence. The IFAS and EFAS analyses indicate a strength score of 2.23 and a weakness score of 0.77. Meanwhile, the EFAS results show an opportunity score of 2.56 and a threat score of 0.72. Based on the SWOT Analysis diagram, Apotek Aditara 2 is positioned in quadrant 1, applying an aggressive strategy by leveraging its strengths and opportunities. The applicable SO strategy for Apotek Aditara 2 in Surabaya includes maintaining a complete and varied product supply, preserving the cleanliness and tidiness of the pharmacy, sustaining preventive healthcare services, upholding good service provision, and establishing collaborations with health centers and doctor's practices.